Origin of two different classes of defective HSV-1 Angelotti DNA. - Kaerner, H C (1979)
During serial passages of Herpes simplex virus (HSV) at high multiplicity of infection, virions containing defective viral DNA accumulate in the progeny. The defective DNA molecules are made up by repeats of restricted portions of the standard viral genome. Two different classes of defective DNA derived from HSV-1 Angelotti (ANG) in independent series of high MOI-passages were studied. The nucleotide sequences contained in the defective DNA were localized on the parental viral genome. One of the two classes contained sequences from non-contiguous sites mapping in unique and in redundant regions of the parental DNA, whereas the second class apparently originates from the S-terminal redundant region of the parental DNA. The localization of defective DNA sequences was complicated by the fact that there exists sequence homology between the S-terminal redundancy and various unique DNA sequences in the L-segment of the HSV-1 ANG genome.